Retinopathy of prematurity - Dammann, Olaf; Hartnett, M. Elizabeth; Stahl, Andreas (Developmental medicine and child neurology, 2023)
Retinopathy of prematurity (ROP) is a devastating neurovascular disease of the retina in newborn infants that can lead to vision deficits or even blindness. In this concise review we discuss our current knowledge about diagnosis, etiology, pathogenesis, intervention, and outcomes of the disease. Major advancements have been made both in categorizing the disease in the new International Classification of Retinopathy of Prematurity, Third Edition classification and in treating severe ROP with anti‐vascular endothelial growth factor (VEGF) agents. New development always creates new questions and opens up new areas of research. We will discuss in this review both the benefits and downsides of the new anti‐VEGF treatment approaches in ROP, especially in light of our improved understanding of the underlying ROP pathophysiology. We also offer pointers to areas where more research is needed. What this paper adds Concise update on all aspects of retinopathy of prematurity (ROP), including advances in understanding and treatment. Benefits and risks of the new treatment method of anti‐vascular endothelial growth factor injections in ROP are discussed. New research areas that deserve attention in the coming years are identified. What this paper adds Concise update on all aspects of retinopathy of prematurity (ROP), including advances in understanding and treatment. Benefits and risks of the new treatment method of anti‐vascular endothelial growth factor injections in ROP are discussed. New research areas that deserve attention in the coming years are identified. This article provides a concise up‐to‐date overview of retinopathy of prematurity and its etiology, pathogenesis, diagnosis, treatment, and outcomes.